The protective role and mechanism of ginkgolide B in regulating mTOR signalling pathway involved in Manganese-induced apoptosis and autophagy in N27 cells - Liyu Su; Shunyu Xiang; Huan Mao; Jiayu Fu; Hongwei Ding; Feng Wang; Lan Zhao; Jianwei Bai; Yuyan Cen; Deyu Zhu; Meng Deng; Yan Li (Ecotoxicology and Environmental Safety)
Ginkgolide B (GB) is a diterpenoid compound found in the leaves of the traditional Chinese medicine plant Ginkgo biloba, which has been shown to have a variety of pharmacological functions. However, the role of GB in Manganese(Mn)-induced apoptosis and autophagy in neuronal cells remains poorly understood. The aim of this study is to investigate the effects of GB on Mn-induced apoptosis and autophagy in N27 cells and further elucidate the mechanism of its protective effects. N27 cells were exposed to MnCl2, GB, mTOR activator, mTOR inhibitor, and autophagy inhibitor, respectively. Cell viability and cytotoxicity were monitored by CCK8 and LDH kits, DA and TH by ELISA, apoptosis by flow cytometry and TUNEL staining, autophagy by MDC staining and mCherry-GFP-LC3B transfection, and autophagy and apoptosis-related proteins by WB. Furthermore, the lentiviral vector was adopted to construct Beclin-1 gene overexpression and knockdown models, and CO-IP was employed to detect the interaction between Beclin-1 and BCL-2. After MnCl2 treatment of N27 cells, cell viability, enhanced apoptosis and autophagy, and inhibited mTOR signalling pathway. Addition of GB to Mn-stained cells was found to effectively alleviate apoptosis and autophagy, particularly, the optimized effect was realized when GB was combined with mTOR activator. The mTOR inhibitor Rapamycin and autophagy inhibitor Bafilomycin A1 could reverse the efficacy of GB; knockdown of Beclin-1 could alleviate MnCl2-induced apoptosis and autophagy-related molecular indices, whereas Beclin-1 overexpression demonstrated the opposite way. It was observed in this study that Mn-induced apoptosis and autophagy in N27 cells were Beclin-1-dependent; GB could mitigate the apoptosis and autophagy by activating the mTOR signalling pathway.